The Effect of Implementation of Government Accounting Standards and Internal Control System on The Quality of Financial Statements of Disdukcatpil District Langkat - Fadli, Ahmad; Nasution, Juliana (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
In the context of accountability, it is necessary to implement an appropriate, clear and measurable financial reporting system in accordance with the principles of transparency and accountability. With the financial reports, both central and regional finances are expected to be managed properly in order to manage public funds in a transparent, economical, efficient, effective and accountable manner. The existence of these financial statements needs to be considered further, the usefulness of the report as a mere obligation without using the financial statements as a source of information to determine and take policies in developing and growing the region. This study uses a method, namely a quantitative approach. This research begins with observations as preparation for the final stage, namely reporting the results of the study. The research time starts from January 17, 2022 until it is finished. This research was conducted directly on the company. The type of data used is Primary data. Primary data is taken from direct observation and then conducting interviews with related parties. The data used are data from interviews. The selected population are employees of DISDUKCATPIL. The results of this study are the effect that occurs between the Government Accounting System and the Financial Statement Quality variable is not statistically significant at the 5% significance level. The effect that occurs between the Government Internal Control System and the Financial Statement Quality variable is statistically significant at the 5% significance level. The Government Accounting System and the Government Internal Control System simultaneously or simultaneously affect the Financial Report Quality variable at a significance level of 5%.